Physical properties of high density panels (HDP) from pine, bamboo and coparticipation of yerba mate (Research, Society and Development, 2020)
The objective of this study was to evaluate the physical properties of high density particleboard (HDP) produced with pine, bamboo and co-participation of yerba mate, by means of mixtures modeling. Particles of bamboo (Phyllosttachys aurea), finely chopped sticks of yerba mate (Ilex paraguariensis) and Pinus taeda wood were used. These particles, in different proportions of mixtures, were glued in a drum-type rotary mixer with Melamine-Urea-Formaldehyde (MUF) resin, handmade molded and pressed in hydraulic press at 120 °C and 60 kgf.cm-2 for 10 minutes, up to the thickness of the 6 mm. The panels were produced with 0.90 g.cm-³ of nominal density and, after pressing, were stabilized in an air-conditioned  environment at 20º C and 65% of the relative humidity. Statistical analysis follows simplex centroid planning, with seven combinations of the three components and three replicates. It was found that the apparently density, moisture content, thickness swelling (2 and 24 hours water immersion), water absorption (2 hours), are explained by the cubic model, while the water absorption (24 hours) are explained by the quadratic model. The materials used made it possible to produce high density particleboard (HDP) with physical properties that varied according to the different mixtures, however, the best results were observed for the panels produced with bamboo and Pinus taeda.